5x + 5 (x - 3) = 15
Question
Updated 8/10/2014 5:29:23 PM
This conversation has been flagged as incorrect.
Flagged by andrewpallarca [8/10/2014 5:27:12 PM]
Original conversation
User: 5x + 5 (x - 3) = 15

Weegy: x=3 (which would make it 15 + 0 = 15)
ramkitten|Points 7278|

User: x + 3 (x - 4) = 2 (x - 2) - 20

Weegy: ((3 / 5) * 0.6) - ((2 / 3) * 0.15) = 0.26 Thanks for asking Weegy.
Jodynoel613|Points 10|

User: 10 - 5 (x - 5) = 4 (x - 1)

User: The sale price of a suit is three-fifths of the original price. Let p denote the original price of the suit. Express the sale price of the suit in terms of p

Question
Updated 8/10/2014 5:29:23 PM
This conversation has been flagged as incorrect.
Flagged by andrewpallarca [8/10/2014 5:27:12 PM]
Rating
3
5x + 5 (x - 3) = 15;
5x + 5x - 15 = 15;
10x = 15 + 15;
10x = 30;
x = 30/10;
x = 3
3
x + 3 (x - 4) = 2 (x - 2) - 20;
x + 3x - 12 = 2x - 4 - 20;
4x - 12 = 2x - 24;
4x - 2x = -24 + 12;
2x = -12;
x = -12/2;
x = -6
3
10 - 5 (x - 5) = 4 (x - 1);
10 - 5x + 25 = 4x - 4;
-5x + 35 = 4x - 4;
-5x - 4x = -4 - 35;
-9x = -39;
x = -39/-9;
x = 13/3

Questions asked by the same visitor
21 (x - 1) + x = 100 - 2 (x - 1)
Question
Updated 2/18/2014 3:26:07 PM
21 (x - 1) + x = 100 - 2 (x - 1)

21x - 21 + x = 100 - 2x + 2

22x -21 = 102 - 2x

22x + 2x = 102 + 21

24x = 123

x = 123/24

X = 41/8
4 - 9x = 29 - 4x
Weegy: 4 - 9x = 29 - 4x; -9x + 4x = 29 - 4; -5x = 25; x = 25/-5; x = -5 User: 3x + 1 = 82 - 6x Weegy: 3x + 1 = 82 - 6x, 3x + 6x = 82 - 1; 9x = 81, x = 81/9, x = 9 User: 4/5x - 1 = 1/5x + 17 Weegy: 4/5x - 1 = 1/5x + 17; 4/5x - 1/5x = 17 + 1; 3/5x = 18; x = 18/(3/5); x = 90/3; x = 30 User: 9n - 6 = 5n - 30 Weegy: 9n - 6 = 5n - 30; 9n - 5n = -30 + 6; 4n = -24; n = -24/4; n = -6 User: 21 (x - 1) + x = 100 - 2 (x - 1) Weegy: 21 (x - 1) + x = 100 - 2 (x - 1); 21x - 21 + x = 100 - 2x + 2; 22x - 21 = 102 - 2x; 22x + 2x = 102 + 21; 24x = 123; x = 123/24 x = 41/8 (More)
Question
Updated 8/10/2014 5:38:45 PM
-4k2(7k2 - 2k + 1)
Weegy: 7 3/4 - 3/8 = 31/4 - 3/8; =62/8 - 3/8; = 59/8, as a mixed number 7 3/8 User: -4k2(7k2 - 2k + 1) please multiply Weegy: 7 3/4 - 3/8 = 31/4 - 3/8; =62/8 - 3/8; = 59/8, as a mixed number 7 3/8 (More)
Question
Updated 8/10/2014 5:39:41 PM
-4k^2(7k^2 - 2k + 1) = -28k^4 + 8k^3 - 4k^2
27,193,364
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
What is Amendments III?
Weegy: The First Amendment prohibits the making of any law respecting an establishment of religion, impeding the free ...
15. What is 26% as a fraction in simplest form?
Weegy: 22% as a fraction in the simplest form is 11/50.
Veto
Weegy: A veto is the power to unilaterally stop an official action, especially the enactment of legislation. ...
S
L
P
P
Points 100 [Total 554] Ratings 0 Comments 100 Invitations 0 Offline
S
L
R
P
R
P
R
Points 94 [Total 554] Ratings 0 Comments 4 Invitations 9 Offline
S
R
L
R
P
R
P
R
R
R
Points 55 [Total 877] Ratings 0 Comments 5 Invitations 5 Offline
S
Points 41 [Total 41] Ratings 0 Comments 11 Invitations 3 Offline
S
Points 16 [Total 33] Ratings 0 Comments 16 Invitations 0 Offline
S
Points 12 [Total 12] Ratings 0 Comments 12 Invitations 0 Offline
S
Points 10 [Total 40] Ratings 1 Comments 0 Invitations 0 Offline
S
Points 1 [Total 1] Ratings 0 Comments 1 Invitations 0 Offline
S
Points 1 [Total 1] Ratings 0 Comments 1 Invitations 0 Offline
S
Points 1 [Total 2] Ratings 0 Comments 1 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.